Non-Dental glass fiber impregnation on flexural strength of fiber reinforced composite - Nilasary Rochmanita Suparno; Siti Sunarintyas; Muhammad Kusumawan Herliansyah (Majalah Kedokteran Gigi Indonesia, 2018)
The availability of dental E-glass fibers for Fiber Reinforcement (FRC) restoration is limited in Indonesia with relatively high cost.Therefore, non-dental glass fibers have been used as an alternative material. The composition of non-dental glass fibers is almost the same with dental E-glass fibers. An important parameter responsible for the strength of FRC is the impregnation of the fibers with resin. Reinforcing fibers are difficult to impregnate with the resin systems of high viscosity. The aim of study is to assess the effect of non-dental glass fibers impregnation using bis-GMA and TEGDMA resin on the flexural strength of FRC. The materials used in the study were non-dental glass fibers (CMAX, China), resin bis-GMA (Sigma-Aldrich, USA) and TEGDMA (Sigma-Aldrich, USA). Three groups of samples consisted of FRC with non-impregnated fibers, FRC with impregnated fibers (bis-GMA:TEGDMA=4:1) and FRC with impregnated fibers (bis-GMA:TEGDMA=1:1). The three groups were tested to determine flexural strength according to ISO 10477. The samples were stored in aquadest at 37 °C for 24 hours prior to flexural strength test. The results were analyzed by one way ANOVA with LSD post hoc test. The results of study showed that the lowest mean of flexural strength (116.16 ± 15.87MPa) was FRC with non-impregnated fiber and the highest mean (151.32 ± 23.74 MPa) was FRC with impregnated fiber (bis-GMA:TEGDMA=1:1). The statistical analysis showed that fiber impregnation had a significant effect (p< 0.05). It can thenbe concluded that non-dental glass fiber impregnation using bis-GMA and TEGDMA resin could increase the flexural strength of FRC and FRC with the impregnated fibers (bis-GMA:TEGDMA=1:1) that had the highest mean of flexural strength.